The naturalist : Theodore Roosevelt, a lifetime of exploration, and the triumph of American natural history - Lunde, Darrin P. (Crown Publishers, 2016)
"The surprising story of our "naturalist president" Theodore Roosevelt and how his lifelong passion for the natural world set the stage for America's wildlife conservation movement. No United States president is more popularly associated with nature and wildlife than Theodore Roosevelt--prodigious hunter, tireless adventurer, and ardent conservationist. We think of him as a larger-than-life original, yet in The Naturalist, Darrin Lunde has located Roosevelt in the proud tradition of museum naturalism. From his earliest days, Roosevelt actively modeled himself on the men who pioneered a key branch of biology through the collection of animal specimens and by developing a taxonomy of the natural world. The influence they would have on Roosevelt shaped not only his audacious personality but his career, informing his work as a statesman and ultimately affecting generations of Americans' relationship to this country's wilderness. Drawing on Roosevelt's diaries and expedition journals and pulling from his own experience as a leading figure in today's museum naturalism, Lunde constructs a thoughtfully researched, singularly insightful history that tracks Roosevelt's maturation from exuberant boyhood hunter to vital champion of serious scientific inquiry"--